2022
DOI: 10.3389/fimmu.2022.839390
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Impairs Immunometabolism and Promotes Naïve T Cell Differentiation to Pro-Inflammatory Th1 CD4+ T Cells

Abstract: CD4+ T cell differentiation to pro-inflammatory and immunosuppressive subsets depends on immunometabolism. Pro-inflammatory CD4+ subsets rely on glycolysis, while immunosuppressive Treg cells require functional mitochondria for their differentiation and function. Previous pre-clinical studies have shown that ethanol (EtOH) administration increases pro-inflammatory CD4+ T cell subsets; whether this shift in immunophenotype is linked to alterations in CD4+ T cell metabolism had not been previously examined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Thus, similar to other leukocytes, such as APCs, Th17 cells use glycolysis for effector inflammatory function; however, when this metabolic pathway is blocked, T cells become Treg cells [ 85 ]. In a recent study, McTernan et al demonstrated through in vitro assay that ethanol alters naive T cell metabolism with an increase in glycolysis and impaired OXPHOS, which disrupts mitochondrial repair processes and promotes Th1 CD4 + T lymphocytes [ 86 ]. Jones et al showed the main metabolic pathways for different functions in human CD4 + and CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, similar to other leukocytes, such as APCs, Th17 cells use glycolysis for effector inflammatory function; however, when this metabolic pathway is blocked, T cells become Treg cells [ 85 ]. In a recent study, McTernan et al demonstrated through in vitro assay that ethanol alters naive T cell metabolism with an increase in glycolysis and impaired OXPHOS, which disrupts mitochondrial repair processes and promotes Th1 CD4 + T lymphocytes [ 86 ]. Jones et al showed the main metabolic pathways for different functions in human CD4 + and CD8 + T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption has been associated with damage to CD4 + T cell immune metabolism, hindrance of mitochondrial repair processes, and the promotion of the differentiation of CD4 + T cells into an in ammatory phenotype 35,36 . Exercise can also in uence lymphocytes in the body, potentially reducing the frequency of aged klRG1 + T cells and helping maintain the proportion of CD4 + naïve T cells, which is indicative of successful rather than maladaptive T cell aging 37,38 . Exercise can also in uence lymphocytes in the body, potentially reducing the frequency of aged klRG1 + T cells and helping maintain the proportion of CD4 + naïve T cells, which is indicative of successful rather than maladaptive T cell aging 39,40 .…”
Section: Analysis Of the Difference In Prevalence Of Lymphopeniamentioning
confidence: 99%
“…Altering differentiation direction of T‐cell subsets is another way that alcohol metabolism intervenes T‐cell functions. Alcohol and catabolic product acetaldehyde have been reported capable of modulating signaling of PI3K/Akt and MAPK pathways via increasing NADP+, skewing the balance between Th1 and Th2 cells towards a Th2‐dominant immune response, leading to decreased Th1‐mediated immune surveillance in the liver, while inhibiting the differentiation of Th1 and Th17 cells 47,48 . This results in a shift toward an anti‐inflammatory response and impaired clearance of pathogens, leading to impaired immune surveillance and increased susceptibility to infection in the liver.…”
Section: Mechanisms Of Aldmentioning
confidence: 99%